Implementing climate-smart agriculture for enhanced food security and resilience. Progress report August 2015. - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This report summarises outcomes from a portfolio of CCAFS projects on climate-smart agriculture (CSA). This particular portfolio was selected for its potential of scaling up CSA, which aims for outcomes on food security, building adaptive capacity and, where appropriate, increasing carbon sequestration and reducing greenhouse gas emissions. The following set of headlines highlight the most significant research results and development outcomes achieved during August 2014 to August 2015, in collaboration with a large number of partners.